Clinically important drug interactions with opioid and non-opioid analgesics - Vezmar-Kovačević Sandra; Vučićević Katarina; Vučenović-Topić Valentina; Rajkovača Zvezdana; Miljković Branislava (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
Patients often seek advise from doctors and pharmacists about pain treatment. Opioid and non-opioid analgesics are the most commonly used drugs in the treatment of pain, but they have potential for pharmacodynamic and pharmacokinetic drug-drug interactions. The risk of central nervous system depression and respiratory depression is increased if opioid analgesics are used with anxiolytics, first-generation antihistamines, and antidepressants. Serotonin syndrome can occur if tramadol and fentanyl are used with selective serotonin reuptake inhibitors (SSRIs), serotonin and noradrenaline inhibitors, monoamino oxidase inhibitors, etc. Decreased elimination of opioid analgesics as a consequence of CYP2D6 and CYP3A4 isoenzyme inhibition can result in their increased efficacy but sedation and respiratory depression have also been reported. Caution is needed when non-steroidal anti-inflammatory drugs (NSAIDs) are used concomitantly with other drugs that cause bleeding such as anticoagulants and SSRIs or drugs that decrease the elimination of NSAIDs by inhibition of CYP2C9. NSAIDs can antagonize the effect of antihypertensives, and interaction with angiotensin-converting enzyme inhibitors may result in renal failure. In comparison with opioid analgesics and NSAIDs, paracetamol has the lowest potential for clinically significant interactions. The prophylactic administration of paracetamol after vaccination should be avoided and patients should be advised not to use alcohol during therapy.